Hacia una redefinición de la feminidad : proyecto social y discurso poético en Rosario Castellanos. - Tubía, Lilia Virginia. (University of Ottawa (Canada), 1998)
All Rosario Castellanos' work (1925-1974) reflects her vital concern: women and their historical relationship of subordination within the system of patriarchy that we can trace through different periods of history. In her varied production of poems, short stories, novels, plays and essays, Castellanos explored in particular the devices that from within the patriarchal logic have undermined women's being, making them develop dependent, unsatisfied subjectivities, always under male tutelage. Within this framework, this study analyses four of the later poems of Castellanos. Our interest is to see how in her quest for a re-definition of femininity, which still has resonance today, Rosario Castellanos seeks alternative ways to define the categories of female and male as traditionally determined by Western Social Imagination. An extensive critical bibliography already exists on Rosario Castellanos, and from the 80s onwards she has been studied more and more within the context of women's studies, gender studies and feminist theory. Some of these studies examine Castellanos' poetry from feminist viewpoints, but practically none of them concentrates exclusively on her poetry. This study attempts to partially fill that gap. (Abstract shortened by UMI.)
Keywords: Literature, Latin American.